The association between problematic smartphone use and the severity of temporomandibular disorders: A cross-sectional study - Pei, Ya-Peng; Li, Han-Chao; Zhong, Jia-Wei; Gao, Xin-Lin; Xiao, Chu-Qiao; Yue, Yuan; Xiong, Xin (Frontiers in Public Health, 2022)
Objective To evaluate the prevalence of different types of temporomandibular disorders (TMD) symptoms in young adults and determine their associations with problematic smartphone use (PSU). Methods The data of the study were collected from local university students through an online questionnaire survey. Demographic information, Fonseca Anamnestic Index (FAI), Smartphone Addiction Scale-Short Version (SAS-SV), and Patient Health Questionnaire-4 (PHQ-4) responses were gathered electronically and analyzed using multiple logistic regression analysis. Results There were 163 male and 307 female respondents were participated in this study. The prevalence of PSU and TMD were 83.6% and 66.4%, respectively. There was a moderate statistical correlation between PSU and TMD among young adults (r = 0.31, p < 0.01). The logistic regression model revealed that the risk of TMD was 1.77 times higher in people with PSU than in those without PSU (OR = 1.77; 95% CI 1.04–3.06). PSU is a risk factor for pain-related TMD (OR = 1.81; 95% CI 1.08–3.04) but not intra-articular TMD. Conclusion Subjects showed high prevalence of both TMD and PSU. People with PSU experienced more severe and frequent pain-related rather than intra-articular TMD symptoms than those without PSU. By reducing the problematic smartphone use, the risk factor of TMD might be avoided.